ANALISIS STAKEHOLDERS DALAM PENGEMBANGAN EKOWISATA DI TAMAN NASIONAL BETUNG KERIHUN KABUPATEN KAPUAS HULU - Muji Listyo Widodo; Rinekso Soekmadi; Hadi Susilo Arifin (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Betung Kerihun National Park (BKNP) is a transboundary conservation area. BKNP region has various attractive ecotourism activities are covered in the context of the nature, culture and 55adventure. But the number of foreign tourists who have visited is still low. BKNP has not been a major tourist destination yet, because the stakeholders have not synergistic in the management of ecotourism in BKNP. The study of stakeholders in accordance with its role and function is urgently needed. This research aims to identify the stakeholders and determine the relationship between stakeholders who are involved in the ecotourism development at BKNP. The data were analyzed using stakeholders analysis methods. There were 23 stakeholders identified involved in the ecotourism development in BKNP. The stakeholder mapping resulted in four as subject (high interest but low influence), six stakeholders as key player (high influence and high importance), eight stakeholders as setter context (high influence but low interest), and five stakeholders as crowd (low influence and low interests). There were three relationships between each stakeholder that were identified, which are communication, cooperation, and coordination.